A defensive mindset: A pattern of social information processing that develops early and predicts life course outcomes. Issue 4 (24th March 2022) - Dodge, Kenneth A.; Bai, Yu; Godwin, Jennifer; Lansford, Jennifer E.; Bates, John E.; Pettit, Gregory S.; Jones, Damon
Abstract: The hypothesis was tested that some children develop a defensive mindset that subsumes individual social information processing (SIP) steps, grows from early experiences, and guides long‐term outcomes. In Study 1 (Fast Track [FT]), 463 age‐5 children (45% girls; 43% Black) were first assessed in 1991 and followed through age 32 (83% retention). In Study 2 (Child Development Project [CDP]), 585 age‐5 children (48% girls, 17% Black) were first assessed in 1987 and followed through age 34 (78% retention). In both studies, measures were collected of early adverse experiences, defensive mindset and SIP, and adult outcomes. Across both studies, a robust latent construct of school‐age defensive mindset was validated empirically (comparative fit index = .99 in each study) and found to mediate the impact of early child abuse (38% in FT and 29% in CDP of total effect) and peer social rejection (14% in FT and 7% in CDP of total effect) on adult incarceration.